Role of Various Estrus Induction and Synchronization Protocols in Influencing Plasma Progesterone, Metabolic Profile and Fertility in Acyclic Buffaloes - Prajapati, JP; Patel, DM; Dhamui, AJ; Patel, JA; Hadiya, KK; Chaudhri, DV (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
A study was carried out under field conditions on 50 acyclic/ anestrus buffaloes to evaluate the efficacy of four standard estrus synchronization protocols, viz., Doublesynch, Estradoublesynch, Ovsynch, and Ovsynch Plus (10 buffaloes in each protocol, and in untreated control group) in terms of estrus induction response, conception rates at induced estrus with FTAI and monitoring plasma progesterone, protein and cholesterol profile at different time intervals during treatment and day 12 post-AI. All the animals received pre-synchronization treatment, i.e., Inj. 100 mg ivermectin s/c, Inj. tono-vita 20 ml, and multi-minerals 1 bolus daily for 7 days. The conception rates obtained at induced estrus (FTAI) were 50.0, 40.0, 30.0 and 50.0 % with Doublesynch, Estradoublesynch, Ovsynch and Ovsynch Plus protocol, respectively. The rests were taken as non-conceived ones. The plasma progesterone concentrations monitored on day 0 (start of treatment), 7/9 (PGF2α injection), 10/12 (FTAI) and on day 12 post-AI revealed significant (p
Keywords: Buffalo; Acyclic; Estrus synchronization; Conception rate; Plasma profile